A Retrospective Analysis of Trends in Influenza Vaccination Uptake at Sukraraj Tropical and Infectious Disease Hospital, Kathmandu, Nepal - Shrestha, Keshari Maya; Rimal, Shikha (Nepalese Journal of Agricultural Sciences, 2025)
Influenza is one of the widespread public health problems. Influenza vaccination rates have fluctuated extensively between 2075 and 2081, influenced by the COVID-19 pandemic and seasonal patterns. Annual rates fell sharply between 2076-77 and 2077-78, most likely due to the redirection of healthcare resources and public reluctance to visit facilities, while recovering by 2080-81 with 208 doses. Monthly data showed peaks in winter and monsoon months like Magh and Asar, while in summer months like Baisakh, the doses are low due to low influenza transmission. The females received more vaccinations due to targeted pregnancy campaigns initially, while the males outgrew them by 2080-81, reflecting post-pandemic behavioral changes. Such trends highlight the effect of the pandemic on vaccination rates, besides underlining adaptive strategies in response to any health crisis and seasonal outbreaks.